Linking Anthropogenic Influence to Landscape Disturbance Patterns. - Berg, Justin (My University, 2009)
This work concentrates on anthropogenic landscape disturbance by investigating the relationship between a small logging trail easement established in 1986 and a subsequent concentrated area of frequent tree fall occurrences thereafter; this areas is now referred to by the landowners as the "dead zone." Results from this study permitted the identification of tree felling as a result of two factors: wind and soil. The techniques employed in the quantitative modeling provide a better understanding of significant geological/geographical features from a physical and anthropogenic perspective. Of equal importance, the results from this study established a systematic and quantitative tool kit to identify tree fell behavior that can be used in a wide variety of other important terrestrial environments.
Color poster with text, images, and charts (Spring 2009)
Keywords: Nature--Effect of human beings on; Forests and forestry--Effect of human beings on; Tree felling; Posters